N-butylphthalide: Neuroprotektor untuk Stroke Iskemik - Clement, Lyon (Cermin Dunia Kedokteran, 2025)
Stroke, especially ischemic stroke, is still one of the most prioritized health problems in Indonesia with an enormous burden and cost. The main strategy to treat ischemic stroke, which is reperfusion therapy by thrombolytic therapy or thrombectomy, has various challenges in its practices, especially regarding the recommended time window due to facility and infrastructure limitations. N-butylphthalide (NBP) is a neuroprotector with the potential ability to improve cerebral microcirculation, protect the blood-brain barrier, protect neurons from apoptosis, induce neurogenesis, and maintain neuron survivability in the condition of ischemic stroke based on preclinical studies. Clinically, NBP showed benefits mainly in improving post-stroke disability. NBP is a promising neuroprotector for better clinical outcomes.